Radical Scavenger Properties of Some 1,2-Dithiol Compounds Against Electropolymerization of Aniline - HADJADJ*, MOHAMMED; DADAMOUSSA, BELKHIR; ABASQ†, MARIE-LAURENCE; SAIDI, MOKHTAR; BURGOT†, JEAN-LOUIS; DARCHEN‡, ANDRÉ (Asian Journal of Chemistry, 2009)
The kinetics of aniline electropolymerization was investigated in acidic H2O/CH3CN solutions and in presence of some 1,2-dithiol compounds. The reactions were studied under cyclic potential scanning to measure the electric charge involved between the redox states of the electrodeposited polymers. The electrochemical growth of electrodeposits was kinetically dependent upon the dithiol. Generally, in presence of 1,2-dithiol compounds the growth of electropolymer was slower than observed for aniline alone. In the presence of 3-aminophenyl-5-(4- methoxyphenyl)-1,2-dithiol the aniline electropolymerization was accelerated and led to an improvement in the conductivity of polymer films. In order to establish the nature of the process, aniline electropolymerization or co-polymerization with the 1,2-dithiol compounds, electrodeposits were prepared on vitreous carbon plates and then analyzed by scanning electron microscopy. The morphology was a fibrillar one and the analysis showed that sulfur element was inside the electrodeposits.